Smoking in the home after childbirth: prevalence, determinants and the relationship to smoking in pregnancy - Orton, Sophie (2016)
Childhood secondhand smoke (SHS) exposure causes substantial ill health and mortality, and poses a significant economic and social burden. This thesis aimed to explore the prevalence and determinants of smoking in the home after childbirth, and to understand the experience and attitudes of mothers who stop smoking during pregnancy but relapse soon after delivery.